Analysis of parameters affecting asphalt mixture performance and new perspectives on the design parameters. (20th June 2018) - Wu, Bangwei; Liu, Liping; Sun, Lijun
Highlights: Factors affecting asphalt mixture performance can be divided into four categories. Compaction effort should be a variable design parameter during mixture design process. The interaction of parameters affecting mixture performances can't be overlooked. Abstract: In this paper, various factors affecting asphalt mixture performance were discussed. First, various factors were divided into four categories: material factors (MF), design factors (DF), compaction factors (CF) and volumetric factors (VF), based on how they influence the performance of the asphalt mixtures. MF referred to the properties of the aggregate, filler and binder. DF were those parameters needed to adjust in order to meet some design specifications. CF were related to the specimen compaction approach and compaction effort when molding asphalt mixture specimen. VF characterized the properties of asphalt mixtures through indices such as air voids (AV), voids in mineral aggregate (VMA), and voids filled with asphalt (VFA). The second section of the paper explored the distinctive effects from these four categories of parameters defined above, based on the study and critical review of historical literatures. Based on the discussions and analyses, the limitation of using VF in controlling asphalt mixture design results, as well as the irrationality of setting compaction effort as constant in the design process were revealed. Finally, suggestion was made that it was necessary to introduce compaction effort as DF in mixture design process, and asphalt mixtures should meet performance-based criterion and specific volumetric requirements by adjusting the MF and DF.